1989
DOI: 10.1128/iai.57.9.2878-2885.1989
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of the 47-kilodalton major membrane immunogen of Treponema pallidum determines its hydrophobicity

Abstract: The 47-kilodalton (kDa) major integral membrane immunogen of Treponema pallidum was recently found to be a proteolipid. Similar two-dimensional electrophoretic mobilities and common hydrophobic properties displayed by the native (T. pallidum) and recombinant (Escherichia coli) 47-kDa antigens suggested that the recombinant antigen also possesses covalently bound lipid. Both intact E. coli and E. coli minicells acylated the 47-kDa antigen; immunoprecipitation with a monoclonal antibody specific for the 47-kDa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…In fact, earlier DNA sequence analysis suggested that the molecule was markedly hydrophilic (absence of membrane-spanning domains) (15). The subsequent finding of acylation (3,4) clarified the previously observed hydrophobic character of the molecule (5,26). However, in the DNA sequence reported by Hsu et al (15), no sequences characteristic of signal peptides or of a bacterial lipoproteinspecific signal peptidase II processing site were readily identifiable in the DNA or corresponding amino acid sequences.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…In fact, earlier DNA sequence analysis suggested that the molecule was markedly hydrophilic (absence of membrane-spanning domains) (15). The subsequent finding of acylation (3,4) clarified the previously observed hydrophobic character of the molecule (5,26). However, in the DNA sequence reported by Hsu et al (15), no sequences characteristic of signal peptides or of a bacterial lipoproteinspecific signal peptidase II processing site were readily identifiable in the DNA or corresponding amino acid sequences.…”
mentioning
confidence: 59%
“…Figure 6 shows that the electrophoretic mobility of the nonacylated form of the protein is similar to that of the native 47-kDa antigen. Previous studies had shown that the 47-kDa antigen migrates as a doublet on SDS-PAGE because of occasional translational readthrough of the first of two stop codons in the mRNA (4). The larger of these two forms of the protein is visible only when the gel is overloaded (4,5).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is proposed that this outer membrane lipoprotein of S. hyodysentenae be designated SmpA (Serpulina membrane protein A) and that the gene that encodes it be designated, smpA. T. pallidum also possesses membrane-located lipoproteins (5,6,31), although these lipoproteins do not appear to be present on the surface of the spirochete (8). On the other hand, the variable lipoproteins (Vmp) of Borrelia hernsii are surface orientated and confer the property of antigenic variation on the organism, thus enabling the organism to evade the immune mechanisms of the host (2,30).…”
mentioning
confidence: 99%